Photochemical Study of Different Thicknesses of Polystyrene Films Containing Ni(II) Complex against photodegradation - Haddad, Raghad (Al-Nahrain Journal of Science, 2019)
Ni (II) with 4-amino-5-(pyridyl)-4H-1,2,4-triazole-3-thiolcomplex was synthesized and used as a photostabilizer for polystyrene (PS) films. Polystyrene has been dissolved with Ni (II) complex in chloroform solvent to form PS films in different thickness (40, 50, 60, 70, and 80 μm), which containing 0.5 w\v% concentration, and casting method was used to remove chloroform. The photostabilization activity of these compounds was determined by monitoring the carbonyl index, weight loss method with irradiation time and morphology study. There are several mechanisms were predict according to the results acquired, depending on the structure of the complex: a) UV. absorber or screening, b) peroxide decomposer, and c) radical scavengers.